Economic potentials of artisanal food processing microenterprises in West Africa: Case of "atta" production in Cotonou (Benin) - Claudia E. Kpossilande; Barthélemy G. Honfoga; Thierry Ferre (Agricultural and Food Economics, 2020)
Rapid population growth and urbanization in West Africa have led to profound changes in the lifestyles and diets of urban dwellers. These changes are marked by greater preference for healthier and more nutritious foods, easy to prepare and to consume while saving time. Hence, the development of small-scale food processing and catering activities in the cities. However, despite its importance, the urban food industry still faces several constraints, mainly the lack of equipment that would save cooking time and increase the nutritional quality of final products for consumers. Promoting optimum food processing technologies and business processes has therefore become a major concern for research and policy-makers. This study was conducted as part of the ICOWPEA research project aimed at assessing the economic and sales potential of artisanal food processing microenterprises that produce "atta," a cowpea fritter or snack, in the city of Cotonou. A sample of twentyseven women-headed microenterprises was randomly selected from a list of 125 recorded in 22 streets distributed across 13 districts of the city. They were interviewed using a structured questionnaire. The survey allowed us to assess how they function, their production costs, and financial performance. The surveyed microenterprises belonged to woman artisans, average age 45, who ran their own businesses. Microenterprises allow many young family members to enter the informal job market. While knowledge is mostly transmitted from mother to daughter and based on learning by doing, very simple processing tools are used. Although mechanical milling is used at some stages of cowpea processing, overall, artisanal "atta" production is a low-profitability business with a return rate of only 11.7%. However, it contributes to feeding the family and rewards family labor that accounts for up to 27.6% of total production cost. In addition to creating jobs for low-income female youth, the activity accounts for a remarkable share of the urban food business sector in Cotonou. Technological upgrading and business empowerment are required for these women to become real entrepreneurs and to overcome the key constraints they face, including the lack of access to credit and absence of improved technologies, training and government recognition. In that respect, appropriate policies are needed to take them out of poverty and make Benin the emerging economy it aspires to be. In particular, a dedicated investment and business development support scheme is required to better meet the growing domestic urban food demand and, in the near future, to envisage the export of stabilized and safer finished cowpea products.
Keywords: 330; Cowpea; "Atta" snacks; Female artisans; Microenterprises; Women; Food processing; Economic performance; Urban poverty reduction